Preferential interaction parameters in biological systems by Kirkwood-Buff theory and computer simulation - Smith, Paul E. (My University, 2007)
Recent results concerning the formulation and evaluation of preferential interactions in biological systems in terms of Kirkwood–Buff (KB) integrals are presented. In particular, experimental and simulated preferential interactions of a cosolvent with a biomolecule in the presence of water are described. It is argued that the preferential interaction parameter defined in a system open to both cosolvent and solvent corresponds to the situation most relevant to the analysis of computer simulation results of cosolvent interactions with proteins and small peptides. Hence, KB theory provides a path from quantities determined from simulation data to the corresponding thermodynamic data.
Keywords: Kirkwood-Buff theory; Lysozyme; Molecular dynamics; Preferential interactions; Urea